Food intake diet and sperm characteristics in a blue zone: a Loma Linda Study. (August 2016) - Orzylowska, Eliza M.; Jacobson, John D.; Bareh, Gihan M.; Ko, Edmund Y.; Corselli, Johannah U.; Chan, Philip J.
Abstract: Objectives: The study examined the effect the life-long vegetarian diet on male fertility and focused on vegetarians living in the Loma Linda blue zone, a demographic area known for life longevity. The objective was to compare sperm characteristics of vegetarian with non-vegetarian males. Study design: The cross-sectional observational study was based on semen analyses of 474 males from 2009 to 2013. Patients categorized themselves as either life-long lacto-ovo vegetarians ( N  = 26; vegetable diet with dairy and egg products), vegans ( N  = 5; strictly vegetables with no animal products) or non-vegetarians ( N  = 443; no diet restrictions). Sperm quality was assessed using a computer-aided sperm analyzer and strict morphology and chromatin integrity were manually evaluated. Results: Lacto-ovo vegetarians had lower sperm concentration (50.7 ± 7.4 M/mL versus non-vegetarians 69.6 ± 3.2 M/mL, mean ± S.E.M.). Total motility was lower in the lacto-ovo and vegan groups (33.2 ± 3.8% and 51.8 ± 13.4% respectively) versus non-vegetarians (58.2 ± 1.0%). Vegans had lowest hyperactive motility (0.8 ± 0.7% versus lacto-ovo 5.2 ± 1.2 and non-vegetarians 4.8 ± 0.3%). Sperm strict morphologies were similar for the 3 groups. There were no differences in rapid progression and chromatin integrity. Conclusions: The study showed that the vegetables-based food intake decreased sperm quality. In particular, a reduction in sperm quality in male factor patients would be clinically significant and would require review. Furthermore, inadequate sperm hyperactivation in vegans suggested compromised membrane calcium selective channels. However, the study results are cautiously interpreted and more corroborative studies are needed.